Synthesis and physical-chemical properties of (3-benzyl-8-propylxanthin-7-yl)acetohydrazide derivatives and their evaluation for antimicrobial and diuretic activities - K. V. Aleksandrova; Ye. K. Mykhalchenko; O. S. Shkoda; D. A. Vasyliev (Zaporozhye State Medical University, 2021)
One of the most important tasks of our indigenous pharmaceutical science is the necessity for new medicines because existing drugs are characterized by various side effects, resistance, high toxicity, and so on. New bioactive molecule synthesis utilizes substances of natural origin as well as chemically modified ones. Thus, the researcher's attention is mainly focused on 3-,7-,8-substituted derivatives of the natural heterocyclic xanthine system, which possess a wide range of pharmacological action. Synthesis of a novel of (3-benzyl-8-propylxanthin-7-yl)acetohydrazides with antimicrobial and diuretic activities described in the paper. The aim of this work is to develop efficient methods for synthesis of (3-benzyl-8-propylxanthin-7-yl)acetohydrazide derivatives, and to study their physical-chemical properties. Materials and methods. Two-hour boiling of propyl 2-(3-benzyl-8-propylxanthine-7-yl)acetate by excess hydrazine hydrate in propan-2-ol medium have yielded the key the key intermediate 2-(3-benzyl-8-propylxanthine-7-yl)acetohydrazide. Further transformation of the latter has led to formation of corresponding acetohydrazide derivatives achieved by the reaction with aliphatic, aromatic, heterocyclic aldehydes, and ketones. The structure and the relative configuration of the synthesized compounds were elucidated by analyzing their physical-chemical data. Results. The synthesis and optimization of reaction conditions of (3-benzyl-8-propylxanthin-7-yl)acetohydrazide derivatives were conducted. The identification of all synthesized compounds was aided by various physical-chemical methods (thin layer chromatography, elemental analysis, IR, and 1H NMR spectroscopy). Conclusions. As a result of synthetic research the preparative synthesis method of (3-benzyl-8-propylxanthin-7-yl)acetohydrazide derivatives possessing antimicrobic, and diuretic activities was developed.